The effect of carbonate mineral additions on biogeochemical conditions in surface sediments and benthic–pelagic exchange fluxes - K. Biçe; K. Biçe; T. Myers Stewart; T. Myers Stewart; G. G. Waldbusser; C. Meile (Biogeosciences)
Coastal sediments are hotspots of biogeochemical processes that are impacting subsurface and overlying water conditions. Fluid composition in sediments is altered through the mineralization of organic matter which, under oxic conditions, further lowers both pH and the carbonate saturation state. As a potential mitigation strategy for this sediment acidification, we explored the effects of mineral additions to coastal sediments. We experimentally quantified carbonate mineral dissolution kinetics of carbonate shells suitable for field application and then integrated these data into a reactive transport model that represents early diagenetic cycling of C, O, N, S, and Fe and traces total alkalinity, pH, and saturation state of CaCO3. Model simulations were carried out to delineate the impact of mineral type and amount added, porewater mixing, and organic matter mineralization rates on sediment alkalinity and its flux to the overlying water. Model results showed that the added minerals undergo initial rapid dissolution and generate saturated conditions demonstrating the potential of alkalinity enhancement in mitigating surface sediment acidification. Aragonite dissolution led to higher total alkalinity concentrations than calcite. Simulations of carbonate mineral additions to sediment environments with low rates of organic matter mineralization exhibited a substantial increase in mineral saturation state compared to sediments with high CO2 production rates, highlighting the environment-specific extent of the effect of mineral addition. Our work indicates that carbonate additions have the potential to effectively buffer surficial sediments over multiple years, yielding biogeochemical conditions that counteract the detrimental effect of low-pH sediment conditions on larval recruitment and potentially increase benthic alkalinity fluxes to support marine carbon dioxide removal (mCDR) in the overlying water.